Socialnopedagoško delovanje učiteljev v poklicni šoli - Berdajs, Andrej; Marovič, Mateja (Revija za elementarno izobraževanje, 2018)
Socio-pedagogical Activity of Teachers in Vocational School. Among students in secondary vocational schools, a large proportion are resistant to school because of negative experiences from previous forms of education and other aggravating factors. Such students face complex difficulties in the school environment. Their resistance to school and achool work also directly affect their lack of success in school. Teachers can, however, improve student behavior if they respond by improving socio- pedagogical activity with students, by creating an inclusive school culture and a positive school climate. In particular, communication between teachers and pupils is important; through this, an appropriate pedagogical relationship is created, which forms the basis for successful achievement of educational goals.DOI: 10.18690/rei.11.4.269-292.2018COBISS-ID: 1541023172